IMPLEMENTASI KEMITRAAN PEMERINTAH-SWASTA DALAM PENGELOLAAN SAMPAH DI KOTA PEKANBARU - April, Muhammad; Alkadafi, Muammar; Ilyas, Ilyas (Universitas Riau Kepulauan, 2024)
Abstract : The waste problem in Pekanbaru City is a social and environmental problem that is currently urgently needed to be resolved. Pekanbaru City Government policy gives authority to third parties, with a public-private partnership (PPP) model in implementing waste management. This research aims to explore the factors causing the ineffectiveness (effectiveness) of waste management in Pekanbaru City using the Public-Private Partnership (PPP) model. The research approach uses qualitative data analysis, data obtained through observation, interviews, relevant documents. Interviews were conducted with key informants, which were then matched or compared with the results of field observations, documents, to produce data credibility. The research results concluded that the public-private partnership (PPP) model was not effective in solving the waste service problem. Unclear contract management between local government (DLHK) and the private sector, lack of space for broad public participation to get involved, public awareness of sorting organic and inorganic waste, discipline in disposing of waste at legal TPSs at predetermined hours is lacking or not even implemented nicely. This is a factor causing ineffective policy implementation. Research suggestions, the policy implementation model uses a complete